Removal of retained upper canine in the middle. Case report - Bienvenido Mesa Reinaldo; José Luis Capote Femenias; Alejandro Díaz Tejeda; Yordanis Boza Mejías (Medisur)
The inclusion of upper canine is one of the most common retentions that occur in permanent teething, this event may be related to that, this is the last tooth to erupt in the lower, also is associated with involution of the jaws, because eruption path is long and complex, often facing unfavorable. A case of a female patient, aged 25, of rural origin, which does not suffer from any disease, which was seen because of discomfort in area 23, ie in the left upper permanent canine. It was noted in the oral examination persistent left superior temporal canine, 63, and periapical and panoramic X-rays showed the presence of 23 included in an intermediate position. It was decided to make a modification of surgical technique with a conservative view of the palatal cortical bone. Was performed successfully including resection of the canine.